2010
DOI: 10.1186/1472-6920-10-4
|View full text |Cite
|
Sign up to set email alerts
|

A survey on the attitudes towards research in medical school

Abstract: BackgroundAn observed decrease of physician scientists in medical practice has generated much recent interest in increasing the exposure of research programs in medical school. The aim of this study was to review the experience and attitudes regarding research by medical students in Canada.MethodsAn anonymous, cross-sectional, self-report questionnaire was administered to second and fourth year students in three medical schools in Ontario between February and May of 2005. Questions were primarily closed-ended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
291
7
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(350 citation statements)
references
References 16 publications
42
291
7
10
Order By: Relevance
“…This lack of skills may arise from inadequate early exposure to the basic concepts of scientific inquiry that serves to limit their later research involvement [4951]. While in some countries students had research exposure before medical school, they still did not feel prepared enough to engage in research [35,47,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of skills may arise from inadequate early exposure to the basic concepts of scientific inquiry that serves to limit their later research involvement [4951]. While in some countries students had research exposure before medical school, they still did not feel prepared enough to engage in research [35,47,50].…”
Section: Discussionmentioning
confidence: 99%
“…Non-institutional barriers included lack of down time, inadequate scientific writing skills, and lack of self-efficacy. Many of the studies [51,56] that investigated factors working against student involvement in undergraduate research cited other key factors such as poor mentorship, lack of role models, and perceived lower salaries of academic physicians. Indeed, quality mentorship is strongly associated with a more positive research experience for students and may bolster interest in a research-oriented career [51,56].…”
Section: Discussionmentioning
confidence: 99%
“…In the neighbouring Karachi, it was observed that only a meagre forty one percent (41%) had taken part in research though most of them were involved in data collecting and computer work. While in a research conducted in Canada, it has shown that 43% of the student had not made significant research contributions [11]. The Faculty of Health and Medical Sciences at the University of Copenhagen noted that several students were interested in research while a very few of them actually had an research experience [12].…”
Section: Resultsmentioning
confidence: 99%
“…[29] In addition, this study revealed lack of scheduled time with their supervisors for research activity and was considered as a strong barrier, which was also found in another study. [26] A study reported that the student would not be able to manage their studying time for research projects and therefore need more supervisor guidance for such activities. [30] Furthermore, lack important research skills and poor writing skills believed to be one of the main obstacles that prevent undergraduate students from publications.…”
Section: Discussionmentioning
confidence: 99%
“…[23] Nevertheless, many barriers have been identified. Studies have shown that the main barriers for not publishing were lack of time, [18,23,24] lack of important research skills, [25] lack of institutional motivation, insufficient training, [26] lack of supervisor guidance, [27,28] and studies results not required to practice medicine. [14] Furthermore, students' perception that the participation in a research project will not allow them to maintain their educational level and affect their academic achievement in terms of their grade point averages.…”
Section: Introductionmentioning
confidence: 99%